Incident Pneumonia In Toddler With The Physical Environment Of The Home Does Not Meet The Requirements - Pudyastuti, Rita Retna; Fau, Piuskosmas; Timisela, Joula; Yermi, Yermi; Hamdanestini, Rischa; Aisyah, Siti; Asmah, Nur (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Globally, pneumonia is one of the diseases that causes morbidity and mortality in low-income countries. Pneumonia is a major cause of death in toddlers and young children. Bacteria, viruses, and fungi are pathogenic agents and play a role in causing pneumonia. The etiology of pneumonia varies based on epidemiological circumstances, comorbidities and whether the pneumonia is community-acquired or hospital-acquired. The aim of this study was to analyze the relationship between the physical environment of the home and the incidence of pneumonia in toddlers in villages. This type of research is analytical quantitative research with a cross-sectional study approach with a sampling technique, namely simple random sampling. Data collection techniques use observation sheets. The data analysis used was univariate analysis and bivariate analysis with the Chi Square test. The results of this study can be concluded that there is a relationship between housing density and the incidence of pneumonia in toddlers. It is expected that the Health Center will always monitor the development of pneumonia cases in toddlers that occur in the Work Area of the Health Center which are caused by the physical environment of the house that does not meet the requirements.